1986
DOI: 10.1001/archderm.1986.01660160030012
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline (Trental) Therapy for the Vasculitis of Atrophie Blanche

Abstract: Fig 3.-Twins aged 3 years. Great toenail of right foot is onychogryphotic and left great toenail is only malaligned. possess a mild variant of great toenail malalign¬ ment.These cases clearly demonstrate the genetic fac¬ tors in this condition. If the dystrophy were due to intrauterine positioning, both great toenails would be dystrophic for the nails would all be dystrophic rather than the curious combination of one onycho¬ gryphotic and one malaligned but otherwise normal nail. We believe that the dystrophy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

1988
1988
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 3 publications
0
8
0
3
Order By: Relevance
“…These studies suggest that the thrombosis found to occur in livedoid vasculitis is part of a primary pathophysiological mechanism. In addition, a number of patients with livedoid vasculitis have responded to antithrombotic and antifibrinolytic agents including heparin,19 tPA,11, 21 pentoxyphylline,8, 9, 33, 34 aspirin and dipyridamole,8, 20 long‐term anticoagulants,6, 12 danazol,17, 38 ketanserin,32 beraprost,37 and prostacyclin 16. A single report of intravenous immunoglobulin in livedoid vasculitis suggested a possible response 33.…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that the thrombosis found to occur in livedoid vasculitis is part of a primary pathophysiological mechanism. In addition, a number of patients with livedoid vasculitis have responded to antithrombotic and antifibrinolytic agents including heparin,19 tPA,11, 21 pentoxyphylline,8, 9, 33, 34 aspirin and dipyridamole,8, 20 long‐term anticoagulants,6, 12 danazol,17, 38 ketanserin,32 beraprost,37 and prostacyclin 16. A single report of intravenous immunoglobulin in livedoid vasculitis suggested a possible response 33.…”
Section: Discussionmentioning
confidence: 99%
“…92–93 It improves membrane flexibility of erythrocytes, reduces platelet aggregation, and decreases vessel fibrinogen concentration by increasing fibrinolytic activity. 79 Although it is indicated mainly for intermittent claudication, it has been useful in the treatment of ischemic ulcers, 94 livedoid vasculitis, 95 stasis ulcers, 94 sickle cell ulcers, 79 necrobiosis lipoidica diabeticorum, 96 and Raynaud's phenomenon. 97 It is noted to have a mild vasodilatory effect.…”
Section: Vascular Drugsmentioning
confidence: 99%
“…118 , 119 Pentoxifylline has been used because of its improving effect on erythrocyte deformability and lowering effect on blood viscosity. 120 , 121 Both aspirin and pentoxifylline have, besides the above‐mentioned properties, a positive effect on rheology and prevent sludge formation. Anticoagulants were first suggested in 1962.…”
Section: Therapymentioning
confidence: 99%